WNT pathway signaling is associated with microvascular injury and predicts kidney transplant failure. Issue 10 (10th May 2019) - Seifert, Michael E.; Gaut, Joseph P.; Guo, Boyi; Jain, Sanjay; Malone, Andrew F.; Geraghty, Feargal; Della Manna, Deborah L.; Yang, Eddy S.; Yi, Nengjun; Brennan, Daniel C.; Mannon, Roslyn B.
Abstract : Microvascular injury is associated with accelerated kidney transplant dysfunction and allograft failure. Molecular pathology can identify new mechanisms of microvascular injury while improving on the diagnostic and prognostic capabilities of traditional histology. We conducted a case‐control study of archived kidney biopsy specimens stored up to 10 years with microvascular injury (n = 50) compared with biopsy specimens without histologic injury (n = 45) from patients of similar age, race, and sex. We measured WNT gene expression with a multiplex quantification platform by using digital barcoding, given the importance of WNT reactivation to the response to wounding in the kidney microvasculature and other compartments. Of 210 genes from a commercial WNT panel, 71 were associated with microvascular injury and 79 were associated with allograft failure, with considerable overlap of genes between each set. Molecular pathology identified 46 biopsy specimens with molecular evidence of microvascular injury; 18 (39%) were either C4d negative, donor‐specific antibody negative, or had no microvascular injury by histology. The majority of cases with molecular evidence of microvascular injury had poor long‐term outcomes. We identified novel WNT pathway genes associated with microvascular injury and allograft failure in residual clinical biopsy specimens obtained up to 10 years earlier. Further mechanistic studies may identify the WNT pathway as a new diagnostic and therapeutic target. Abstract : Using a multiplex quantification platform with digital barcoding, the authors identify WNT pathway genes associated with microvascular injury and allograft failure in residual clinical biopsies performed up to 10 years ago.